Challenges Experienced by Health Professionals in Implementing the Family Integrated Service Post in Public Health Center; A qualitative study - Elisa Sulistia Fitri; Mely Ratnasari Thiu; Mira Utami Ningsih (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2023)
The Family Integrated service post is a program that aiming to provide accessible health services to all over the villages and/or sub-villages in the province. The family integrated service post (FISP) targeting pregnant women, breastfeeding mothers, babies, adolescent, productive age, and elderly. Healthcare workers faced some challenges during the provision of integrated service post, either from their co-workers or from the communities. The challenges perceived have significant impact on the quality of services as well as the provision of integrated service post program. Hence, this study was aimed to investigate the challenges perceived by health professionals during the implementation of the FISP in PHC of Sembalun. This study used a qualitative interview design and adopted constructivists paradigm. The study used purposive stratified sampling technique to determine the sample. Three midwives, three nurses, a health promotion practitioner, and two nutritionists were participated in the study. This study identified four main challenges experienced by health professionals in public health center of Sembalun. The challenges are communities’ schedule, lack of awareness, unsupported of essential tools, and staff shortage. Participants verbally conveyed that these challenges have significant effects on the provision of family integrated service post. Further study is needed to explore more challenges that could impede health services as well as study regarding the impact of these challenges